2020
DOI: 10.3892/or.2020.7869
|View full text |Cite
|
Sign up to set email alerts
|

TCF7 knockdown inhibits the imatinib resistance of chronic myeloid leukemia K562/G01 cells by neutralizing the Wnt/β‑catenin/TCF7/ABC transporter signaling axis

Abstract: Clinical resistance to ABL tyrosine kinase inhibitor (TKI) imatinib remains a critical issue in the treatment of chronic myeloid leukemia (CML). Transcription factor 7 (TCF7) is one of the main Wnt/β-catenin signaling mediators. Previous studies have shown that TCF7 is vital for tumor initiation, and targeting TCF7 can reduce drug resistance in many types of cancer. However, the role of TCF7 in CML imatinib-resistant cells is unclear. In the present study, we analyzed the transcriptomic data from CML clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…1 D). The Wnt/β-catenin pathway signaling has been shown to propagates the initiation and progression of HLF [ 22 ], and TCF7 is essential for the typical WNT/β-catenin pathway [ 44 ]. However, the relationship between TCF7 and HLF pathogenesis is unclear and needs further study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 D). The Wnt/β-catenin pathway signaling has been shown to propagates the initiation and progression of HLF [ 22 ], and TCF7 is essential for the typical WNT/β-catenin pathway [ 44 ]. However, the relationship between TCF7 and HLF pathogenesis is unclear and needs further study.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factor 7 (TCF7, also known as TCF1) is one of the members of the TCF/LEF transcription factor family and participates in the transcriptional regulation of Wnt/β-catenin signal [ 1 , 3 ]. Emerging evidence has shown that TCF7 is involved in tumorigenesis and development [ 2 , 35 , 44 ], sepsis-induced renal injury [ 39 ], heart development [ 40 ], and cardiac hypertrophy [ 26 ]. However, the roles and underlying mechanism of TCF7 in HLF have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…However, no distinct effect on IC-50 value was caught (Additional file 2 : Figure S2D). Previous investigations have linked the Wnt pathway with imatinib-resistance [ 34 , 35 ], the relevant markers including CTNNB1 and c-Myc were detected using a western blot assay, accordingly. The data demonstrated a discernible loss of both CTNNB1 and c-Myc in K562/G01 cells which circCRKL was knocked down (Additional file 2 : Figure S2E).…”
Section: Resultsmentioning
confidence: 99%
“…Progeny cells from these clones have a strong ability to proliferate and lose the ability to differentiate into relatively mature blood cells. Recent studies showed that the protective upregulation of Wnt/β-catenin and ABC transporter signals induced by imatinib treatment is neutralized by knockdown of transcription factor 7 (TCF7), one of the main Wnt/β-catenin signaling mediators [Zhang et al, 2020]. While uncontrolled cell proliferation that precedes cancer involves several cell clones, the crucial event leading to cancer is the selection and further expansion of a single clone, characterized by a "carcinogenic advantage" [Wright, 2002].…”
Section: The Fight Against Cancer Variability: Cancer Evolution and Drug Resistancementioning
confidence: 99%